Foreign Exchange Intervention : A Dataset of Public Data and Proxies - Adler, Gustavo (IMF Working Papers; Working Paper ;, 2021)
Foreign exchange intervention (FXI) is a highly debated topic. Yet, comprehensive and comparable data on FXI is hard to find. This paper provides a new dataset of FXI covering a large number of countries over the period 2000-20 at monthly and quarterly frequencies. It includes publicly available data for about 40 countries and carefully constructed proxies for 122 countries. Proxies are focused on both spot and derivative transactions that alter the central bank's foreign currency position and account for a wide range of central bank operations, including vis-a-vis residents, the first proxy to do so to our knowledge. The paper discusses the merits of the new proxy relative to coarser measures traditionally used like the change in reserves, and potential definitional differences with published data. The paper also presents stylized facts using our newly constructed FXI proxies.